National allegiance and sporting citizenship: identity choices of 'African' footballers. Issue 1 (2nd January 2020) - Storey, David
Abstract: Sport provides a useful lens through which the complexities of national identity and citizenship can be explored. Competitors don the national colours, salute the anthem and face the flag, becoming the embodiment of the wider imagined community, carrying the nation's hopes and dreams. Traditionally, those who compete for countries have usually been born and raised there or have lived there for sizeable periods of their lives. In recent years, however, the selection by international sports teams of competitors born in other countries has become increasingly common. A combination of national citizenship requirements, residency qualifications and the shifting regulations of sporting bodies has seen an increasing number of 'transfers' of national allegiance. In football, a number of African teams draw heavily on their European-born diasporas, a reflection of a colonial past and deeply entrenched migration routes. Alongside this, European national teams, most notably France and Belgium, are composed of many players with close family links to Africa. These scenarios serve to draw attention to the often complex, multi-layered and contingent nature of national identity.